A Mathematical Model for Determining the Facility Layout Plan of a Plastic Injection Factory - Kaklıkkaya, Harun; Çetin, Fatma; Uyumaz, Şule; Saraç, Tuğba (Enthusiastic : International Journal of Applied Statistics and Data Science, 2023)
In this study, a mathematical model has been developed to make the facility layout planning of the annex building, which is being built right next to the old building of a factory that produces plastic parts. Some or all parts of the departments, such as injection machines, semi-finished products, product, raw material warehouses, molding room, and paint shop in the old building of the factory can be moved to the new building. Nevertheless, some cannot be moved. Since injection machines use cranes for electricity, plumbing, and mold transport, relocation is very costly. Different layouts are proposed with the developed mathematical model for seven scenarios that allow and do not allow partitions of the departments. The proposed layout plans were compared in terms of the total carrying costs of the products and the carrying costs of the sections. In this way, the factory has been presented with a significant cost reduction opportunity.